Unlocking IT Excellence: A Deep Dive into Design Factors for Successful IT Implementation with COBIT - Muda Dwi Nugraha, Faaris; Zikri Nugroho, Fathoni; Fadhli Taqdirul Jabbar, Muhammad (Universitas Pendidikan Indonesia (UPI), 2024)
COBIT 2019 formulates 11 design factors that must be considered in designing IT governance. One of these design factors is IT Implementation Methods, which refers to the methods used by organizations to implement IT. This article aims to discuss the importance of IT implementation methods in IT governance, various types of IT implementation methods that organizations can choose from, and factors to consider in selecting the appropriate IT implementation method. The article employs a qualitative approach with literature review as the method of data collection. The results of the analysis indicate that the chosen IT implementation method can influence various aspects of IT governance, such as alignment with business strategy, risk management, resource availability, and organizational leadership commitment. The article recommends that organizations carefully consider these factors when selecting an IT implementation method that aligns with their needs and environment.